PNH is a debilitating, fatal but treatable disease: same disease, different clinical presentations - Sahin, Fahri (Am J Blood Res, 2015)
Paroxysmal nocturnal hemoglobinuria (PNH) is a disease characterized by chronic persistent hemolysis, multi-organ damage and eventually multiple organ failure. PNH develops as a result of increased sensitivity to complement due to an acquired deficiency of certain glycosylphosphatidylinositol (GPI)-linked proteins. The clinical presentation of PNH varies greatly from one patient to another. We present three cases of PNH with different clinical presentations to illustrate the debilitating nature of the disease, possible fatal outcomes, and the need to timely diagnosis and targeted therapy. These cases also underline the need for increased awareness of PNH among relevant healthcare specialties. PNH should be considered as a differential diagnosis in patients with unexplained abdominal pain, dyspnea, renal failure, thrombosis and non-immune hemolytic anemia.